Performance Characteristic of the beta-Human Chorionic Gonadotropin Assay on the Access 2 for Its Use in Doping Control - Kang, Min-Jung; Lee, Hyeim; Shin, Sang Mi; Yoo, Hye Hyun; Kwon, Oh-Seung; Jin, Changbae; Chung, Bong Chul (대한화학회, 2010)
The objective of this study was to validate performance characteristics of the Access 2 (Beckman coulter) system for hCG assays for use as a confirmation test for doping control. The Access 2 assay was linear up to 500 IU/L. The correlation coefficient was higher than 0.999, and the sensitivity of the linearity was 0.82. There were no false positive or false negative cases. LOD was 0.59 IU/L. The method was robust when performed by different people. Repeatability and reproducibility were below 7%. We compared reproducibility and recoveries of Access 2 and Elecsys 2010. Access 2 demonstrated higher reproducibility than Elecsys 2010. Recoveries (accuracy) of Access 2 were between 85 and 105%. Recoveries for Elecsys 2010 were between 91 and 104%.